Nav channel binder containing a specific conjugation-site based on a low toxicity β-scorpion toxin. Issue 1 (December 2017) - Kubota, Tomoya; Dang, Bobo; Carvalho-de-Souza, Joao; Correa, Ana; Bezanilla, Francisco
Abstract Voltage-gated sodium (Nav) channels play a key role in generating action potentials which leads to physiological signaling in excitable cells. The availability of probes for functional studies of mammalian Nav is limited. Here, by introducing two amino acid substitutions into the beta scorpion toxin Ts1, we have chemically synthesized a novel binder [S14R, W50Pra]Ts1 for Nav with high affinity, low dissociation rate and reduced toxicity while retaining the capability of conjugating Ts1 with molecules of interests for different applications. Using the fluorescent-dye conjugate, [S14R, W50Pra(Bodipy)]Ts1, we confirmed its binding to Nav1.4 through Lanthanide-based Resonance Energy Transfer. Moreover, using the gold nanoparticle conjugate, [S14R, W50Pra(AuNP)]Ts1, we were able to optically stimulate dorsal root ganglia neurons and generate action potentials with visible lightvia the optocapacitive effect as previously reported. [S14R, W50Pra]Ts1 is a novel probe with great potential for wider applications in Nav-related neuroscience research.